2017
DOI: 10.1002/prot.25266
|View full text |Cite
|
Sign up to set email alerts
|

Experimental conformational energy maps of proteins and peptides

Abstract: We have presented an extensive analysis of the peptide backbone dihedral angles in the PDB structures and computed experimental Ramachandran plots for their distributions seen under a various constraints on X-ray resolution, representativeness at different sequence identity percentages, and hydrogen bonding distances. These experimental distributions have been converted into isoenergy contour plots using the approach employed previously by F. M. Pohl. This has led to the identification of energetically favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
(171 reference statements)
1
3
0
Order By: Relevance
“…The results for polyglycine, on the other hand, indicate a planar conformation. The results are in close agreement with previously published Ramachandran plots of GLY 3 and ALA 3 . MD simulations snapshots in water show the most probable conformations of a part of the polypeptides. (e–g) Ramachandran plots of ASN 13 , GLU 13 , and LYS 13 at a stretching force of 1300 pN show that all peptides except glycine adopt nonplanar most probable states.…”
Section: Resultssupporting
confidence: 90%
“…The results for polyglycine, on the other hand, indicate a planar conformation. The results are in close agreement with previously published Ramachandran plots of GLY 3 and ALA 3 . MD simulations snapshots in water show the most probable conformations of a part of the polypeptides. (e–g) Ramachandran plots of ASN 13 , GLU 13 , and LYS 13 at a stretching force of 1300 pN show that all peptides except glycine adopt nonplanar most probable states.…”
Section: Resultssupporting
confidence: 90%
“…The protein backbone is often modeled as a freely-jointed chain due to its ability to rotate around N-Cα and Cα-C bonds in every monomer. If, however, the backbone rotation is forced to occur only in one direction, as would be the case with consistent application of the torque force, eventually some dihedral angles phi and psi would be pushed into sterically disallowed positions, which are described in Ramachandran plots [ 74 , 75 ], limiting the rotation in those positions and making possible the accumulation of tension in the peptide backbone. An example of such possible local torsion-induced strain in the native structure of bacterial methyl transferase has been described [ 76 ].…”
Section: How To Fold Thermodynamically Unstable Proteinsmentioning
confidence: 99%
“…Conformational properties of Alanine residue in peptides have been investigated extensively with theories [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ] and experiments [ [21] , [22] , [23] , [24] ] to understand the protein folding and development of the force fields [ 7 , [25] , [26] , [27] ]. Theoretical studies reported that Ala dipeptide models, Ac-Ala-NH 2 and Ac-Ala-NHMe, favor the inverse γ-turn (γ′) and extended ( ε or β S ) conformation in the gas phase ( Fig.…”
Section: Introductionmentioning
confidence: 99%